Real-life effectiveness of rituximab in different subsets of idiopathic inflammatory myopathies - Stefano Stano; Fabio Cacciapaglia; Laura Coladonato; Giuseppe Lopalco; Florenzo Iannone; Marco Fornaro (Reumatismo)
Objective. Idiopathic inflammatory myopathies (IIM) are heterogeneous autoimmune diseases including dermatomyositis (DM), polymyositis (PM), immune-mediated necrotizing myopathy (IMNM), and anti-synthetase syndrome (ASS). Treatment typically involves high-dose corticosteroids (CCS) and conventional synthetic disease-modifying antirheumatic drugs (csDMARD). Rituximab (RTX) has shown effectiveness in refractory cases. Our real-life study aimed to assess the safety and effectiveness of RTX treatment in IIM patients.